Infrared thermography to evaluate thermoplastic composites under bending load. (15th December 2015) - Boccardi, Simone; Carlomagno, Giovanni Maria; Meola, Carosena; Simeoli, Giorgio; Russo, Pietro
Abstract: Thermoplastic matrix-based composites are becoming ever more popular due to their many advantages over both metals and thermoset matrix-based composites. In particular, they can be tailored by the addition of a compatibilizing agent to the matrix, which allows to create a multitude of materials. Of course, each of these materials requires characterization for an appropriate exploitation. In this context, infrared thermography represents a viable inspection means since it is non-contact, non-intrusive and can be used to monitor the entire existence of a product, from its manufacturing process to completion as well as in-service life. In this work, several composite materials based on a polypropylene matrix, which may be neat, or modified by addition of a certain amount of a specific compatibilizing agent, and reinforced with glass, or jute, woven fibres are considered and subjected to cyclic bending tests. Infrared thermography is used for monitoring the bending event.